Contextual Learning to Improve Student Social Science Activities and Learning Outcomes (Study at SMKN 1 Kuala Lobam Series) - Jefri Tampubolon; Nuril Huda; Muhajir Muhajir (Global Education : International Journal of Educational Sciences and Languages, 2025)
This study aims to evaluate the effectiveness of the application of the contextual learning model in improving student activities and learning outcomes in Natural and Social Sciences (IPAS) subjects at SMKN 1 Seri Kuala Lobam. Contextual learning emphasizes the relevance of the subject matter to students' real lives, allowing them to construct understanding through more meaningful practical experiences. The research method used is qualitative research with a descriptive approach. Data were collected through observations, interviews, and documentation from students and teachers involved in the application of this model. The results showed that contextual learning significantly increased students' activities in group discussions, experiments, and projects, as well as their learning outcomes, both in cognitive, affective, and psychomotor aspects. This learning also helps students develop problem-solving and critical thinking skills that are indispensable in the world of work. Thus, contextual learning has proven to be an effective approach in improving the quality of learning at SMKN 1 Seri Kuala Lobam.